Genetic Programs of Structural Evolution of Hybrid Electromechanical Objects - V. F., Shinkarenko; Iu, Gaidaienko; Al-Husban, Ahmad N (International Journal of Engineering and Technology, 2012)
In this paper the interconnected genetic models defining algorithms of intrageneric synthesis of hybrid electromechanical structures are considered. The authors analyze the space of admissible crossing and define the variety of genetically admissible classes of hybrid structures. The recommendations about the use of models in problems of a structural prediction and innovative synthesis of new versions of hybrid electromechanical objects are given.